Conceptualization of Digital Image Processing for the Evaluation of Pavement Surfaces in Costa Rica - Herra Gómez, Luis Diego (2025)
The timely attention of a road system through minor maintenance activities, such as potholes repair techniques and crack sealing, is a practice recognized for its good cost-benefit ratio, by preventing the pavement from an accelerated deterioration dueto the effect of climate and transit, reducing the need of major and expensive interventions. However, although minor maintenance activities can be very beneficial, in Costa Rica, identifying road segments that requirethesetypes of interventions is a work that could be biased to the criteriaof those who perform the visual auscultation of deteriorations, and depending on the route that is being evaluated, it could be a dangerous activity in terms of road safety.Given this scenario, it is necessary to have automated processes that allow generating an inventory of preventive maintenance needs in an agile, objective and safe manner. To do this, there are currently several alternatives that allow automating the count of preventive maintenance needs of a road, being digital image processing one of the most used.The digital image processing allows, by using algorithms applied to a road photographic record, to define intervention criteria for minor maintenance activities, in order toidentify with greater certainty the deteriorations under a certain threshold of severity present in a road.In this way, the digital image registry could be considered as a very valuable input to improve efficiency in terms of the investment made in a certain road system, without forgetting that this type of tools are a complement that should not replace the technical criteria of th e professionals in charge of the road management system.